DELAYED CORD CLAMPING (DCC) PADA PELAKSANAAN 60 LANGKAH APN DI TPMB PERMATA HATI MATESIH - Agustin, Kurnia; Hastutik (Jurnal Ilmiah Maternal, 2025)
Delayed Cord Clamping (DCC), also known as cord clamping delay, is a technique suggested by healthcare workers in Indonesia, especially for normal delivery. Instead of being held or cut right away, this delay is usually done for about thirty seconds to two minutes after the baby is born. Delayed cord clamping (DCC) allows for placental transfusion into the newborn and results in an increase in the newborn's blood volume at birth. Although it has been supported by various medical regulatory bodies. TPMB Permata Hati Matesih is one of the health facilities that implements Delayed Cord Clamping (DCC) when implementing 60 steps of APN. This study aims to find out the DCC that has been implemented in the health facility. The research using a quantitative descriptive type with a cohort approach will be carried out in 2024 at TPMB Permata Hati Matesih. Using total sampling. Results: Of the 30 normal deliveries (APN), 27 delivered using Delayed Cord Clamping (DCC).